The hypoxia‐inducible miR‐429 regulates hypoxia‐inducible factor‐1α expression in human endothelial cells through a negative feedback loop. Issue 4 (30th December 2014) - Bartoszewska, Sylwia; Rochan, Kinga; Piotrowski, Arkadiusz; Kamysz, Wojciech; Ochocka, Renata J.; Collawn, James F.; Bartoszewski, Rafal
Abstract : Hypoxia‐inducible factors (HIFs) 1 and 2 are dimeric α/β transcription factors that regulate cellular responses to low oxygen. HIF‐1 is induced first, whereas HIF‐2 is associated with chronic hypoxia. To determine how HIF1A mRNA, the inducible subunit of HIF‐1, is regulated during hypoxia, we followed HIF1A mRNA levels in primary HUVECs over 24 hours using quantitative PCR. HIF1A and VEGF A ( VEGFA ) mRNA, a transcriptional target of HIF‐1, increased 2.5‐ and 8‐fold at 2‐4 hours, respectively. To determine how the mRNAs were regulated, we identified a microRNA (miRNA), miR‐429, that destabilized HIF1A message and decreased VEGFA mRNA by inhibiting HIF1A. Target protector analysis, which interferes with miRNA‐mRNA complex formation, confirmed that miR‐429 targeted HIF1A message. Desferoxamine treatment, which inhibits the hydroxylases that promote HIF‐1α protein degradation, stabilized HIF‐1 activity during normoxic conditions and elevated miR‐429 levels, demonstrating that HIF‐1 promotes miR‐429 expression. RNA‐sequencing‐based transcriptome analysis indicated that inhibition of miRNA‐429 in HUVECs up‐regulated 209 mRNAs, a number of which regulate angiogenesis. The results demonstrate that HIF‐1 is in a negative regulatory loop with miR‐429, that miR‐429 attenuates HIF‐1 activity by decreasing HIF1A message during the early stages of hypoxia before HIF‐2 is activated, and this regulatory network helps explain the HIF‐1 transition to HIF‐2 during chronic hypoxia in endothelial cells.—Bartoszewska, S., Kochan, K., Piotrowski, A., Kamysz, W., Ochocka, R. J., Collawn, J. F., Bartoszewski, R. The hypoxia‐inducible miR‐429 regulates hypoxia hypoxia‐inducible factor‐1α expression in human endothelial cells through a negative feedback loop. FASEB J. 29, 1467‐1479 (2015). www.fasebj.org